Produção de biossurfactantes/bioemulsificantes por leveduras isoladas de efluentes de uma indústria de laticínios - Andrea de Souza Monteiro (2009)
New strains of biosurfactants producing yeast were isolated from a sewage treatment plant of a dairy product industry. These strains were identified as belonging to the genus Trichosporon, Galactomyces, Geotrichum and Candida based on the sequences of the D1/D2 region of 26S rDNA and ITS1-ITS2 from the rDNA gene. Among the 32 yeast isolated, 13 showed emulsifying activity (E24) after 2 months of incubation. The emulsified solution remained stable for up to 2 months of incubation, with values ranging from 7.32% to 78.52%. The highest emulsification rates were observed in emulsions produced by supernatant cultures of Trichosporon loubieri CLV 20, Geothricum sp. CLOA 40, T. montevideense CLOA 70 and T. montevideense CLOA 72, with values of E24 to 71.29%, 77.45%, 65.80% and 78.52%, respectively. These strains reduced the surface tension of the growth medium to values that ranged from 40.85 mN/m to 52 mN/m. The surfactants contained different types of fatty acids, with a prevalence of molecules containing 18 carbons (39.56% to 85.77% of the total solution content). The analysis of monosaccharides present in the surfactants indicated the prevalence of xylose for biosurfactants produced by CLV20 and CLOA70, manose for biosurfactant produced by CLOA72 and galactose for biosurfactant produced by CLOA40. The emulsifying activity was dependent on the carbon source in the culture medium, with higher activity observed when sunflower oil and glucose were used. The emulsifying activity of the biosurfactant presented values above 70% at concentrations of 3 mg/mL to 3.5 mg/mL, and above 75% at concentrations above 4.5 mg/mL. The emulsifying activity was stable in a wide range of pH (2-10), and after heat treatment at 100 °C. The emulsifying activity was also stable after the addition of 30% of the salts NaCl, KCl and NaHCO3. The biosurfactant was able to emulsify a wide range of hydrophobic substrates. The critical micellar concentration estimated was in 2.2 mg/mL, giving a surface tension of water of 48.4 mN/m. This study also, evaluated the effect of yeast biosurfactant T. montevideense CLOA72 in the formation of biofilms by Candida albicans CC isolated from apical tooth canal. The greatest reduction (87.41%) in the formation of biofilms were observed at a concentration of 16 mg/mL. The interaction of cells of C. albicans CC with biosurfactant characterized was by isothermal titration calorimetry and zeta potential. The process of saturation of the cells of C. albicans by the addition of 1.3 to 5.1 is endhotermic ((Ho = +1284  5.1 Cal/mg.OD600.) occurring with a high increase of entropy (S o = +10635,0 Cal/mg.OD600). The rate of caloric energy released from the minimum concentration of saturation has decreased sharply, indicating a saturation of the cell-biosurfactant. The rate of caloric energy released from the minimum inhibitory concentration decreased sharply, indicating cell saturation by the biosurfactant. The zeta potential of the cell surface were monitored as a function of the concentration of the biosurfactant added to cell suspension. The data suggest that the net surface charges of the cells is partialy neutral, since the value of zeta potential ranging between -16 mV to - 6 mV during the titration. These changes of the surface can contribute to the inhibition of initial adherence of cells of C. albicans in hydrophobic surface. The biosurfactant produced by T. montevideense CLOA72 did not have any cytotoxic effect in HEK 293A cell line at the concentrations of 0.25 to 1 mg/mL. The treatment with the biossurfactant CLOA72 reduced the adhesion of C. albicans 18 to buccal cells in 85.2%. This study suggests a possible application of biosurfactant produced by T. montevideense CLOA72 in inhibiting the formation of biofilms on plastic surfaces and inhibition of adherence to biological surfaces (cells of the host) by strains of C. albicans.